THE PERFORMANCE OF THE PROJECT COALITION IN THE UK CONSTRUCTION INDUSTRY A CONCEPTUAL OPTIMISATION MODEL - Robby Soetanto; David G. Proverbs; Patricia Cooper (Civil Engineering Dimension, 2000)
The UK construction industry has long been criticised for engendering adversarial relationships among project participants. The nature of interrelationships ultimately determines overall project performance%2C in terms of finished product%2C and levels of performance and satisfaction for the participants. To investigate these interrelationships%2C the performance and satisfaction of each individual participant must be considered. Better understanding of the interrelationships should help reduce adversarialsm and improve the performance and satisfaction of each participant. The possible interrelationships that may exist are discussed based on %91soft knowledge%92 approaches%2C i.e. psychology%2C organisational behaviour and sociology. It is concluded that the performance of each participant is interdependent and essential towards project performance. Two levels of satisfaction%2C which determine the quality of working relationships between participants%2C are postulated. The first level of satisfaction %28i.e. satisfaction on achieving organisational objectives%29 is%2C to some extent%2C dependent on the second level of satisfaction %28i.e. satisfaction on the performance of the other participants%29. Therefore%2C within the construction project coalition%2C each participant has to be satisfied with the performance of the other participants if harmonious working relationships are to be sustained. Based on these%2C a conceptual model for optimising the relationships between main participants of the project coalition is presented. Abstract in Bahasa Indonesia : Coalition+participants%2C+Interrelationships%2C+Performance%2C+Satisfaction+